EVALUASI PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH DI KOTA MANADO - Waney, Theo Rudolf; Morasa, Jenny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2015)
Local Revenue is among the sources of funding of local government, and is needed in carrying out the task of government and in development. Act 32 of the local government established local tax as one of the local revenue and can be developed according to the conditions of each region. One of the sources of local revenue for the government of the city of Manado is the entertainment tax. Manado city as the center of government, trade and tourism has many places of entertainment, but the extent of the contribution of the entertainment tax on local revenue need to be investigated. The purpose of this study was to evaluate whether the effect of the entertainment tax to the local revenue of Manado. This study used secondary data obtained from the Revenue Affairs of Manado. The method used to evaluate the influence of the entertainment tax is the rate of growth. Data entertainment tax of Manado city between 2010-2014 was analyzed, and it shows the variation of revenue and was not significantly affect local revenues of Manado. Variations in entertainment tax revenues likely caused by fluctuations in entertainment activities in the city of Manado. Tax entertainment revenues are relatively small shows the effort to seek potential entertainment tax are not fully in the city of Manado. The government need to provide facilities for investment in sectors related to entertainment and at the same time optimizeeffort to seek and to collect entertainment tax in the city of Manado. Future studies need to deepen and broaden the acquisition of information and data relating to entertainment tax in the city of Manado.